Caddie Woodlawn - Brink, Carol Ryrie 1895-1981 (The Macmillan Company, 1935)
Chronicles the adventures of eleven-year-old Caddie growing up with her six brothers and sisters on the Wisconsin frontier in the mid-nineteenth century.